Glow in the dark tumor: enhanced near-ir visualization and destruction of cancer with a self-quenched theranostic - Güler, Selen İrem; Altan, Cem Levent; Demircioğlu, Emine Esma; Verimli, Nihan; Abisoğlu, Beyza; Bayraktaroğlu, Çiğdem; Erdem, Sultan Sibel (My University, 2025)
Late diagnosis is one of the major obstacles for the treatment of breast cancer which can be overcome with a system offering sensitive imaging and selective therapeutic effect. In this study, we developed a “dark-bright” multifunctional drug delivery system bringing real-time imaging and non-invasive therapy together. Theranostic ability of the system was delivered by Verteporfin (VP), serving as a fluorescence probe and a photosensitizer. To create a “dark state” system via self-quenching ability of VP, it was immobilized onto the superparamagnetic iron oxide nanoparticle (SPION) surface. Upon cellular uptake of the “dark state” system, release of VP led to fluorescence regain, switching the system to “bright state” after which photodynamic therapy (PDT) was initiated to lead to cell death. Theranostic feature of the system was evaluated in MCF-7 and MDA-MB-231 cell lines. Following internalization, fluorescence signal was increased up to ∼56-fold in MCF-7 cells. The IC50 value decreased ∼20-fold and ∼117-fold in MCF-7 and MDA-MB-231 cell lines, respectively. Moreover, the system significantly inhibited migration in the highly aggressive MDA-MB-231 cell line and induced apoptosis by caspase-3 activation. The developed “dark-bright” system is a promising multifunctional drug delivery vehicle with extraordinary theranostic features for the detection and destruction of micro tumors.
Keywords: Breast Cancer; Fluorescence Quenching; Near-IR Imaging; Photodynamic Therapy; Superparamagnetic Iron Oxide Nanoparticle; Theranostic Agent